Commission 37: Star Clusters and Associations - Hatzidimitriou, Despina; Lada, Charles J.; Sarajedini, Ata; Cannon, Russell D.; Cudworth, Kyle McC.; Da Costa, Gary S.; Deng, LiCai; Lee, Young-Wook; Sarajedini, Ata; Tosi, Monica (2009)
Star clusters are valuable tools for theoretical and observational astronomy across a wide range of disciplines from cosmology to stellar spectroscopy. For example, properties of globular clusters are used to constrain stellar evolutionary models, nucleosynthesis and chemical evolution, as well as the star formation and assembly histories of galaxies and the distribution of dark matter in present-day galaxies. Open clusters are widely used as stellar laboratories for the study of specific stellar phenomena (e.g., various emission-line stars, pulsating pre-MS stars, magnetic massive stars, binarity, stellar rotation, etc.). They also provide observational constraints on models of massive star evolution and of Galactic disk formation and chemical evolution.